Synthesis, characterization and catalytic activity of novel large network polystyrene-immobilized organic bases. Issue 130 (17th December 2015) - Tassi, Marco; Bartollini, Elena; Adriaensens, Peter; Bianchi, Luca; Barkakaty, Balaka; Carleer, Robert; Chen, Jihua; Hensley, Dale K.; Marrocchi, Assunta; Vaccaro, Luigi
Abstract : In view of searching for efficient solid catalysts to be used in environmentally friendly reaction conditions, novel gel-type cross-linked polystyrenes functionalized with diethylamine and 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene, have been prepared. Abstract : In view of searching for efficient polymeric supports for organic bases to be used in environmentally friendly reaction conditions, novel gel-type cross-linked polystyrenes functionalized with diethylamine and 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene, have been prepared. The structural properties and morphology of these catalysts have been determined by extensive solid state NMR experiments, FTIR spectroscopy and SEM/TEM microscopy. SPACeR-supported bases were found to exhibit high catalytic activity in the epoxide ring opening by phenols. A range of β-substituted alcohols have been readily and regioselectively synthesized.